Kinematic analysis of the technique for elite male long-distance speed skaters in curving - Yuda, J.; Yuki, M.; Aoyanagi, T.; Fujii, N.; Ae, M. (Journal of Applied Biomechanics, 2007)
The purpose of this study was to investigate technical factors for maintaining skating velocity by kinematic analysis of the skating motion for elite long-distance skaters during the curve phase in official championship races. Sixteen world-class elite male skaters who participated in the 5,000-m race were videotaped with two synchronized high-speed video cameras (250 Hz) in a curve lane by using a panning DLT technique. Three-dimensional coordinates of the body and blades during the first and second halves of the races were collected to calculate kinematic parameters. In the group that maintained greater skating velocity, the thigh angle during the gliding phase of the left stroke during the second half was greater than that during the first half, and the center of mass was located more forward during the second half. Thus, it was suggested that long-distance speed skaters should change the support leg position during the gliding phase in the left stroke of the curve phase under fatigued conditions so that they could extend the support leg with a forward rotation of the thigh and less shank backward rotation.